Education–occupation mismatch and its wage penalties: Evidence from Indonesia - Padang Wicaksono; Imelda Theresia; Badra Al Aufa (Cogent Business & Management, 2023)
AbstractOvereducation poses a significant challenge in the job market, impacting both job mobility and wage. This study aimed to examine the influence of overeducation experience on two key factors, including 1) the probability of experiencing overeducation again in the current job and 2) the level of wage obtained from the current job. We use data from four surveys of National Labor Force Survey (SAKERNAS): February 2017, 20 August 17, February 2018, and August 2018. We employed the Multinomial Logistic Regression and a Fixed Effect Model analysis. The results showed that workers who had previously experienced overeducation in their past jobs faced a 31.64% probability of re-experiencing it. This probability was lower than the likelihood of transitioning to a matched job, which stood at 67.35%, hence, overeducation served as a transitional phase toward obtaining a suitable job. Additionally, this study found a wage disparity of 16.2% between workers with overeducation experience and those with matched experience when transitioning to a matched job. Interestingly, no wage difference was observed between the two groups when transitioning to overeducation jobs. In conclusion, training programs should be performed to enhance the productivity of new workers to enable them to adapt more quickly to the work environment and avoid wage penalties.